Role of sphingolipid metabolism in neurodegeneration. Issue 1 (3rd July 2020) - Alaamery, Manal; Albesher, Nour; Aljawini, Nora; Alsuwailm, Moneera; Massadeh, Salam; Wheeler, Michael A.; Chao, Chun‐Cheih; Quintana, Francisco J.
Abstract: Sphingolipids are a class of lipids highly enriched in the central nervous system (CNS), which shows great diversity and complexity, and has been implicated in CNS development and function. Alterations in sphingolipid metabolism have been described in multiple diseases, including those affecting the central nervous system (CNS). In this review, we discuss the role of sphingolipid metabolism in neurodegeneration, evaluating its direct roles in neuron development and health, and also in the induction of neurotoxic activities in CNS‐resident astrocytes and microglia in the context of neurologic diseases such as multiple sclerosis and Alzheimer's disease. Finally, we focus on the metabolism of gangliosides and sphingosine‐1‐phosphate, its contribution to the pathogenesis of neurologic diseases, and its potential as a candidate target for the therapeutic modulation of neurodegeneration. Abstract : In this review, we discuss the role of sphingolipid metabolism in neurodegeneration, evaluating its direct roles in neuron development and health, and also in the induction of neurotoxic activities in CNS‐resident astrocytes and microglia in the context of neurologic diseases such as multiple sclerosis and Alzheimer's disease. Finally, we focus on the metabolism of gangliosides and sphingosine‐1‐phosphate, its contribution to the pathogenesis of neurologic diseases, and its potential as a candidate target for the therapeutic modulation of neurodegeneration.